The relationship between posttraumatic growth and cognitive emotion regulation strategies in hemodialysis patients - Zahra Arjeini; Sakineh Moghaddam Zeabadi; Fariba Hashemi Hefzabad; Saeed Shahsavari (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND AIM: Posttraumatic growth following traumas such as chronic illnesses can occur in some people. The psychological factors, such as cognitive emotion regulation (CER), can influence its formation. CER is a type of coping strategy that helps to efficiently deal with trauma. Due to the importance of the topic and the lack of sufficient studies on posttraumatic growth and CER in hemodialysis patients, this study aims to investigate the relationship between posttraumatic growth and CER in hemodialysis patients. METHODS: This is a descriptive study performed on hemodialysis patients in Bou Ali and Velayat hospitals in Qazvin. One hundred and sixty-two patients were selected by the convenience sampling method, and Garnefski Cognitive Emotion Regulation Questionnaire (α =0.92) and Tedeschi Posttraumatic Growth Questionnaire (α =0.96) were used. Data were analyzed using Pearson correlation and ANOVA tests. RESULTS: The results showed that the majority of the hemodialysis patients experienced some degree of posttraumatic growth. The participants achieved high scores in the domains of spiritual development and communication with others. Moreover, posttraumatic growth was positively and significantly correlated with CER (r = 0.67, P < 0.001). CONCLUSIONS: Hemodialysis provides the basis for the positive mental reactions known as posttraumatic growth in hemodialysis patients. Nurses and other authorities can use this phenomenon to adapt to illness and care planning.